THE EFFECTIVENESS OF MICROSOFT OFFICE 365 AS AN ONLINE ENGLISH LEARNING MEDIA - Marudut Bernadtua Simanjuntak; Muchlas Suseno; Samsi Setiadi (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This study aims whether: 1) Microsoft Office 365 is more effective than conventional methods in teaching writing; 2) Microsoft Office 365 is more effective than other online learning media ;3) There is an increasing interest in language learning; and 4) there is an interaction between teaching methods and students' creativity in learning English. This quasi-experimental research was conducted at Saint Peter's Middle School in the 2020/2021 academic year. The sample of this study has six classes, namely the experimental class which is taught using Microsoft Office 365 and the use of Zoom as an online meeting. Each class consists of 17-22 students, with a total sample value of 60 students. Samples were obtained using cluster random sampling technique. The results showed that there was an increase in the average score and implied that Microsoft Office 365 is an effective method in teaching writing and is suitable to be applied to those who have high creativity. Keywords: Office 365, Microsoft, Learning Media, English Learning